The useful past in negotiation: Adolescents' use of history in negotiation of inter-group conflict (UCL Press, 2017)
Much of the concern with young people's historical knowledge centres on factual attainment or disciplinary skills. However, relatively little attention is paid to the relevance that young people attribute to history and how they use the past, and various social representations of history, to relate to the present. Research in this realm tends to emphasize the impact of collective memory narratives on individuals, rather than individuals' agency in using them. In this article, I will examine the ways 155 Jewish and Arab Israeli adolescents related the past to the present as they discussed the Jewish-Arab conflict and its resolution. Discussants made diverse references to the past: from family history, via biblical allusions and collective memories, to formal, schooling-based historical documents. Individuals used these references to the past to negotiate the present and future of inter-group relations. Furthermore, they made strategic use of references to others' narratives. Thus historical knowledge and collective narratives, which are usually perceived as constraining and structuring learners' perceptions, can be seen as repositories of resources and affordances.